BBX16 mediates the repression of seedling photomorphogenesis downstream of the GUN1/GLK1 module during retrograde signalling. Issue 1 (11th February 2022) - Veciana, Nil; Martín, Guiomar; Leivar, Pablo; Monte, Elena
Summary: Plastid‐to‐nucleus retrograde signalling (RS) initiated by dysfunctional chloroplasts impact photomorphogenic development. We have previously shown that the transcription factor GLK1 acts downstream of the RS regulator GUN1 in photodamaging conditions to regulate not only the well established expression of photosynthesis‐associated nuclear genes ( PhANGs ) but also to regulate seedling morphogenesis. Specifically, the GUN1/GLK1 module inhibits the light‐induced phytochrome‐interacting factor (PIF)‐repressed transcriptional network to suppress cotyledon development when chloroplast integrity is compromised, modulating the area exposed to potentially damaging high light. However, how the GUN1/GLK1 module inhibits photomorphogenesis upon chloroplast damage remained undefined. Here, we report the identification of BBX16 as a novel direct target of GLK1. BBX16 is induced and promotes photomorphogenesis in moderate light and is repressed via GUN1/GLK1 after chloroplast damage. Additionally, we showed that BBX16 represents a regulatory branching point downstream of GUN1/GLK1 in the regulation of PhANG expression and seedling development upon RS activation. The gun1 phenotype in lincomycin and the gun1‐ like phenotype of GLK1OX are markedly suppressed in gun1bbx16 and GLK1OXbbx16 . This study identified BBX16 as the first member of the BBX family involved in RS, and defines a molecular bifurcation mechanism operated by GLK1/BBX16 to optimise seedling de‐etiolation, and to ensure photoprotection in unfavourable light conditions.